Garantizar los derechos humanos y las libertades en el contexto de la pandemia covid-19 - Serhii Kivalov (Universidad Hemisferios, 2020)
The study is devoted to the establishment of the current state of ensuring of human rights and freedoms in Ukraine while counteracting the spread of the Covid-19 pandemic taking into account the institutional and legal basis of the quarantine regime, transformations of ensuring of human rights and freedoms and the rights of participants in administrative procedures. Close attention is drawn to the impossibility of restricting human rights and freedoms that go beyond the goals of Covid-19 dissemination. In carrying out this study, general philosophical and special methods of scientific knowledge were used, namely the methods of: system analysis, dialectical, formal-logical and structural-functional, as well as some empirical methods. The practical significance of the study is that its results are relevant for domestic legislators and entities that carry out public administration in the field of health care against the background of updating trends in the response to the Covid-19 pandemic. A number of measures have been proposed to develop a strategy to counter the spread of the Covid-19 pandemic; creation of subjects of public administration, the competence of which will include ensuring the state policy in the field of ensuring the proper condition and maintaining the mental health of the population; implementation of the concept of electronic justice (e-court) as the only possible mechanism to ensure effective protection of the rights, freedoms, and interests of man and citizen in the face of the Covid-19 pandemic.